PERANAN INTELLECTUAL CAPITAL TERHADAP RANKING BANK PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Permatasari, Anita; Yuniarsih, Nia (Universitas 17 Agustus 1945 Surabaya, 2021)
The shift in bank functions from intermediary functions to fee-based income activities depends on the human resources of a bank, so the banking sector must change the way it runs its business towards a knowledge-based business. Knowledge based business emphasizes the strategic role of science (and the development of science encourages the birth of intellectual capital (IC). Banks with high intellectual capital are expected to have better performance and can improve bank financial performance and are an attraction to attract investors. This study aims to determine the role of intellectual capital on the ranking of banking companies listed on the Indonesia Stock Exchange for the period 2010-2016. This research data uses secondary data with a sample of banking companies listed on the Indonesia Stock Exchange for the period 2010 to 2016. The sample in this study used a purposive sampling method.The result of this study is that the intellectual capital performance of banking companies listed on the Indonesia Stock Exchange from 2010 to 2016 is included in the category of commond performers with s VAIC™ core between 3.9962 and 2.5037.